1991
DOI: 10.1016/s0006-291x(05)81333-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and enhancement of eukaryotic gene expression by potential non-B DNA sequences

Abstract: In a transient or constitutive expression assay we have examined the effect of non-B DNA sequences d(CA)40 and d(CAAAAATGCC)n on gene expression in eukaryotic cells. These sequences were cloned adjacent to the weak eukaryotic promoter (CGTATTTATTTG) and located upstream from the coding sequence of galactokinase enzyme. Recombinants were micro-injected in cultured cells (Chinese hamster fibroblasts R1610, mutant gal-K-) and expression levels have been determined. The alternating purine-pyrimidine tract found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Alternatively, non-B DNA has been implicated in regulation of gene expression (Delic et al, 1991;van Holde and Zlatanova, 1994). The BCL2 mbr forms triplex DNA under physiological conditions and this non-B DNA is a critical structure for cleavage within the BCL2 mbr that leads to the t(14;18) translocation (Raghavan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, non-B DNA has been implicated in regulation of gene expression (Delic et al, 1991;van Holde and Zlatanova, 1994). The BCL2 mbr forms triplex DNA under physiological conditions and this non-B DNA is a critical structure for cleavage within the BCL2 mbr that leads to the t(14;18) translocation (Raghavan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…50,51) Moreover, several studies have found a relationship between the rotational orientation of the curved DNA relative to the promoter and its ability to enhance transcription. 16,49,52) The sequences of the bent DNA sites in the promoter region of the R. americana DNA puff B-2 gene, B. hygida DNA puff C4 and B10 genes (BhC4-1 and BhB10), and T. pubescens DNA puff C4B gene (TpC4B) are shown in Fig.…”
Section: Sequence Analysis Of the C3-22 Amplicon Bent Dna Sitesmentioning
confidence: 99%
“…7b) suggests that the bending in the promoter proximal region causes a narrow minor groove that co-localizes with the TATA box, and which has been reported to promote the association between the TATA box and the TATA box binding protein [Kim et al, 1993]. Analyses in prokaryotic and eukaryotic cells have shown that the promoter strength is dependent, in part, on the intensity of the curvature [Plaskon and Wartell, 1987;Delic et al, 1991]. Moreover, several studies have pointed out a correlation between the rotational orientation of the curved DNA relative to the promoter and its ability to enhance transcription [McAllister and Achberger, 1989].…”
Section: Detailed Computer Analysis Of the Representative Proximal Anmentioning
confidence: 99%